A New Attribute Encryption Anonymity Algorithm in Cloud Computing Environment. (21st July 2022) - Zhao, Cuirong; Chen, Yan
Abstract : In order to solve the security problem of privacy information exposed by plaintext access strategy in cloud computing environment, this paper proposes a new attribute encryption anonymity algorithm which can be hidden and updated. The algorithm proposed in this paper hides the access policy attribute information through a randomized technology, which can support full hiding of the policy, and the prevention and control are more flexible. The experimental results show that, compared with the previous decryption algorithms, under the premise of the same attributes, the encryption time decreases in a few seconds. When the number of attributes is 1, the encryption time decreases by 10 s, and when the number of attributes is 10, the encryption time decreases by about 100 s, and the efficiency is greatly improved.